A randomized controlled trial of fresh frozen plasma for treating venom‐induced consumption coagulopathy in cases of Australian snakebite (ASP‐18). Issue 7 (15th July 2013) - Isbister, G. K.; Buckley, N. A.; Page, C. B.; Scorgie, F. E.; Lincz, L. F.; Seldon, M.; Brown, S. G. A.; ,
Summary: Background: Venom‐induced consumption coagulopathy (VICC) is a major effect of snake envenoming. Objectives: To investigate whether fresh frozen plasma (FFP) given after antivenom resulted in more rapid correction of coagulation. Patients/Methods: This was a multicenter open‐label randomized controlled trial in patients with VICC of FFP vs. no FFP within 4 h of antivenom administration. Patients (> 2 years) recruited to the Australian snakebite project with VICC (International Normalized Ratio [INR] > 3) were eligible. Patients were randomized 2 : 1 to receive FFP or no FFP. The primary outcome was the proportion with an INR of < 2 at 6 h after antivenom administration. Secondary outcomes included time from antivenom administration to discharge, adverse effects, major hemorrhage, and death. Results: Of 70 eligible patients, 65 consented to be randomized: 41 to FFP, and 24 to no FFP. Six hours after antivenom administration, more patients randomized to FFP had an INR of < 2 (30/41 [73%] vs. 6/24 [25%]; absolute difference, 48%; 95% confidence interval 23–73%; P = 0.0002). The median time from antivenom administration to discharge was similar (34 h, range 14–230 h vs. 39 h, range 14–321 h; P = 0.44). Seven patients developed systemic hypersensitivity reactions after antivenom administration – two mild and one severe (FFP arm), and three mild and one severe (no FFP). One serious adverse event (intracranial hemorrhage and death) occurred in an FFP patient with pre‐existing hypertension, who was hypertensive on admission, and developed a headache 6 h after FFP administration. Post hoc analysis showed that the median time from bite to FFP administration was significantly shorter for non‐responders to FFP than for responders (4.7 h, interquartile range [IQR] 4.2–6.7 h vs. 7.3 h, IQR 6.1–8 h; P = 0.002). Conclusions: FFP administration after antivenom administration results in more rapid restoration of clotting function in most patients, but no decrease in discharge time. Early FFP administration (< 6–8 h) post‐bite is less likely to be effective.